John and Elaine Steinbeck at the Whaler's Festival - unknown:::Creator::::::::::::
John Steinbeck sits at the center of a table looking over at an unknown man with a bandana covering his face. Elaine Steinbeck stands at the far left behind the same man at the Whaler's Festival in Sag Harbor, New York. Original in safe